Higher Education Choice in China: Social Class, Gender, Parental Involvement and Educational Inequality - Su Hnin Aye (Debrecen University Press, 2022)
Bibliography of the review book: Sheng, X. (2014). Higher Education Choice in China: Social Class, Gender, Parental Involvement and Educational Inequality. Routledge. 173 pp., ISBN: 978-0-415-84309-6. https://doi.org/10.4324/9781315814254